Collegiate Athletes Engaging in Activism: Perceptions of Social Justice Causes and Support from Significant Social Agents - Martin, Eric; Kluch, Yannick; Mac Intosh, Andrew; Kujala, Shelanda (Sport Social Work Journal, 2022)
Recently, collegiate athletes have used their platform to promote positive social change. Some possibilities for the increase of activism is athletes’ perceptions of societal issues and support from key social agents. However, these perceptions have been largely unexplored. The current study aimed to address those gaps by investigating collegiate athletes’ perceptions and investigating if various demographic characteristics influence the likelihood of activism engagement. Participants (n = 4,473) completed self-report scales on social justice causes and perceived support. For this sample, athletes who identified as male, Black, and More than One Race engaged in activism at a higher rate than expected and a majority of participants viewed all social issues as social justice causes. In terms of support, athletes viewed higher levels of general support than instrumental support and approval for engaging in activism and rated parents, friends, and teammates as most supportive in all three support categories. Activists, compared to non-activists, were more likely to view social issues as social justice related and rated most social agents as more approving of their own activism. Findings indicate that perceptions of social issues and support from social agents, especially non-sport social agents, might be one reason for collegiate athletes’ participation in activism.